Smoking Prevalence and Difficulties to Quitting Among National Heart Institute Patients, Visitors, and Workers (Egypt) - Safwat, Wael; Mahrous, Mary Rabea; Zarif, Bassem (European Journal of Health Sciences, 2022)
Purpose: The study aims to overview the smoking habits, their prevalence, and their correlation with socio-cultural determinants by screening smoking in the national heart institute population. Methodology: A cross-sectional study was conducted in the form of a face-to-face survey. The interviews were carried out by a well-trained team of interviewers, using a survey according to a stratified random sampling approach. The study design was mainly about meeting up to about 300 health care workers and 300 patients visiting the clinics in the national heart institute. Then, start to gather information from them if they smoke and learn more about the type of smoking, they do and their smoking habits. The survey included questions for smokers about quitting trials and their reasons for sticking to smoking. After that, the interviewers tried to raise awareness about the negative impact of tobacco. The next step was to try to advise these smokers to quit. Findings: The study cohort was 160 visitors (36%), 82 employee (19%), 76 nurses (17%), 64 patients (14%), 41 physician (9%) and 20 technician (5%). Regarding the education level, 63% had primary school education, 17% had a university level, and 15% were illiterate. Smoking prevalence was 60% of the patients, 45% of the visitors, and 30% of the health care workers. In the study sample, smokers were more likely to have diabetes (P0.071), to be hypertensive (P0.034), and to have a history of heart disease (P 0.004). They were more likely to be males (P<0.001). There was no significant difference between smokers and non-smokers regarding geographical residence or educational level. Smokers are more likely to be aware of smoking hazards, including heart problems, COPD, cancer, and E.D (P<0.001). Recommendations: This cross-sectional survey study showed only the association, therefore, the cause, pathogenesis, and effect were not evaluated. The study recommend further research with pre specified outcomes.